Combination technology of ceramic microfiltration and biosorbent for treatment and reuse of tannery effluent from different streams: response of defence system inÂ EuphorbiaÂ sp. - Priyankari Bhattacharya; Sourja Ghosh; Aniruddha Mukhopadhyay (International Journal of Recycling of Organic Waste in Agriculture)
Background: The present study was undertaken to evaluate the efficiency of combined technology involving ceramic microfiltration and biosorbent for the treatment of tannery effluent from different streams, viz. composite effluent, effluent from primary clarifier and secondary clarifier. The membranes were prepared from a cost-effective composition of alumina and clay. Results: The effluents had high organic loading of 12,895, 3,890 and 410 mg/L, respectively, in terms of chemical oxygen demand (COD). Apart from these, the effluents consisted of toxic heavy metals, turbidity, biochemical oxygen demand (BOD), etc. It was observed that COD reduction was about 96.5% for effluent 1, 96.6% for effluent 2 and 96.9% for effluent 3. Considerable reduction in suspended solids, total nitrogen, and total organic carbon was obtained. Turbidity for all three types of effluent was below 1 NTU. The average flux value for effluents 1, 2 and 3 was about 13, 19 and 24 L/m2 /h (LMH), respectively. Response of the antioxidative defences of Euphorbia hirta was observed which resulted in considerable decrease in the activity of peroxidase, superoxide dismutase and catalase. Conclusions: The treatment resulted in the reduction of toxicity thereby restoring normal activity when compared to control values. Changes in various biochemical parameters like protein, amino acid, carbohydrate, DNA, RNA and chlorophyll content were observed.